(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers chose to study the crime rate of physical injury during the pandemic in Barangay Pasong Putik because since COVID-19 came, our country has suffered from myriad crises with low and irregular incomes. Some people lost their jobs, and the global economic crisis greatly affected the financial crisis. These ongoing changes are affecting all aspects of life. There is a particular need for research among the Barangay Pasong Putik as these barangays are particularly affected. Physical violence is a willful, intentional, and malicious act committed by a person against another individual. Individuals who threaten violence or otherwise engage in provocative conduct towards co-workers, clients, vendors, or other individuals ordinarily are held at least committed it. During this pandemic time, most families are at home because of the implementation of the government stay at home to not spread the COVID-19 virus, which can lessen the physical violence. This research brief aims to provide initial observations about the crime rate of physical injury in Barangay Pasong Putik to prevent the rise of crime. The researchers used descriptive research and interviewed authorities and residents in the barangay to gather primary information. The study concluded that the police officers and barangay officials are much more knowledgeable about the crime rate of physical injury than the barangay residents. The three group respondents agree about juveniles witnessing violence in their neighbourhood and that adults become violent due to frustration from losing jobs. Stress in terms of mental health was regarded as "serious" because of the pandemic. The study’s findings show that the barangay acquires city ordinances to protect and maintain public safety and implement the purok leaders to enhance the Barangay Pasong Putik. The barangay volunteer peacekeeper officers should continue to encourage their work efficiently and effectively to improve their performance as peacekeepers to keep the barangay area safe. Lastly, the barangay and authorities shall provide services and activities that engage the public to strengthen the relationship and communication with the residents.